2018
DOI: 10.3389/fpsyt.2018.00056
|View full text |Cite
|
Sign up to set email alerts
|

Serious Suicide Attempts: Systematic Review of Psychological Risk Factors

Abstract: BackgroundOne of the main obstacles in studying suicide risk factors is the difference between cases in which the individual died by suicide and those in which the individual engaged in suicidal behavior. A promising strategy that overcomes this obstacle is the study of survivors of serious suicide attempt (SSA), i.e., an attempt that would have been lethal had it not been for the provision of rapid and effective emergency treatment. Serious suicide attempters are epidemiologically very much like those who die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 74 publications
3
91
1
2
Order By: Relevance
“…These additional predictors include socio-demographics, clinical and psychosocial variables such as depression, substance abuse, mental anguish, communication difficulties, interpersonal problems, and impulsivity. 5,6 However, personality traits have been shown repeatedly to be the strongest variables related to suicidality, 7 and an extensive review showed that PDs, based on DSM classifications, place individuals at significantly greater risk for suicide. 8 Cluster B PD, especially borderline PD, was identified as the strongest risk factor for suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…These additional predictors include socio-demographics, clinical and psychosocial variables such as depression, substance abuse, mental anguish, communication difficulties, interpersonal problems, and impulsivity. 5,6 However, personality traits have been shown repeatedly to be the strongest variables related to suicidality, 7 and an extensive review showed that PDs, based on DSM classifications, place individuals at significantly greater risk for suicide. 8 Cluster B PD, especially borderline PD, was identified as the strongest risk factor for suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…Depression, alcohol abuse, hopelessness, and prior suicide attempts are associated with medical severity (Bostwick, Pabbati, Geske, & McKean, ; Swahn & Potter, ; Trakhtenbrot et al, ; Wilcox, Conner, & Caine, ). However, results from previous studies vary because of different definitions of medical severity, and only a few studies compare high lethal attempters to low lethal attempters with sufficient sample sizes (Gvion & Levi‐Belz, ). Considering the scarcity of research on this subject, it is still unclear which factors are most associated with high medical severity in suicide attempts.…”
mentioning
confidence: 99%
“…It is known that SB is a complex disorder, which involves many environmental, behavioral, neurobiological, and genetic factors (Gvion & Levi‐Belz, ; Speed, Drapeau, & Nadorff, ). Researchers of suicide behavior are looking for predisposing (distal) and precipitating (proximal) factors (Conejero, Olie, Courtet, & Calati, ; Gerada, ; Gvion & Levi‐Belz, ; Speed et al, ). Besides, there are several biological, genetic, and environmental abnormalities have been reported in SB, but it is not clear which ones are risk factors (Fiori et al, ; Schneider et al, ).…”
Section: Discussionmentioning
confidence: 99%